LOVE OF GOD IN THE WORLD OF THE THOUGHT OF ABU’L-HASAN EL-KHARAKANI - Ahmet Emin SEYHAN (Fırat University, 2019)
Almighty Allah had created human beings and jinns to recognize Him, to love and worship. Those who have intellect will have to find Almighty Allah who created them perfectly and appreciate Him the best way. The main reason is that the scripture which the people will read, learn and guide it, take as a rol model prophet and use the intellect, will and ability. Abu'l-Hasan al-Kharakani Turkish-Islamic scholar and a great mystic, who used all these resources which Almighty Allah bestowed in place and effectively, found Almighty Allah, connected to Him with great love and has been in the effort to attain the consent of Him. El-Kharakani had not separate from the line of truth and justice in order to win the love of Almighty Allah throughout the whole life and showed his sincere in this love by taking the example of Prophet. According to him, a true lover constantly contemplates Allah and knows that he comes from the God and knows it again return to Him and does not value the world and contents and does not rely on worldly practices and continues to be take permanent,